Axure prototyping blueprints : become an Axure master! Explore designs and interactions by leveraging adaptive views, AxShare plugins, repeaters, and more /: become an Axure master! Explore designs and interactions by leveraging adaptive views, AxShare plugins, repeaters, and more. (2015) - Krahenbuhl, John Henry
No abstract available